Pergeseran Persepsi Keadilan di Kalangan Muslim dalam Arisan Indeks - Abdul Hamid (Asy-Syari’ah : Jurnal Hukum Islam, 2016)
The development of arisan indeks in the life of Moslems of Karangdoro-Tegaljati-Banyuwangi, indicates a new perception of justice in the context of arisan tradition. The main concern of this research is understanding the new perception of justice. This research is a qualitative research applying sociological and ethical Approaches. The data was reached by the techniques of interview, observation, and document study. The data was analyzed using the rational choice theory and the general perspective of contextual ethics as the theoretical framework. One of the results of this research is that the perception of justice of the oslem participants of the arisan indeks is rational and contextual in its character. One of the principles of the Moslems’ perception is that the value of justice in the context of arisan indeks relates to not only the nominal of money but also, and more importantly, the substantive value of money.